Psychology and professional gamers in esports: thematic analysis and research agenda - García Naveira, Alejo; León Zarceño, Eva; González García, Carlos (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The goals of this study are to do a bibliographic review and establish study topics on Psychology and professional gamers in esports, as well as finding out possible researching ways about it. The search was done in Science Direct databases, PubMed and PsycINFO. The total amount was 101 documents published between 2012 and the 13 of June of 2020. From these documents 24 were selected as representatives. The analyzed studies were mainly based on 8 different subjects: psychological training, personality characteristics, team processes, negative consequences of esports, professional career, benefits of esports, psychological skills and processes and invisible training. The Journal Psychology Applied to Sport and Physical Exercise is one of the main contributors to this subject. In conclusion, an exhaustive review shows a growing interest in the subject of esports and its relationship with the field of Psychology, as well as the future lines of research that have been opened.